Temuan Dan Rekomendasi Dari Praktik Mengajar di Sekolah Dasar Dalam Meningkatkan Pengajaran Pendidikan Kewarganegaraan - Dea Khairum; Detya Mopalanda Sianipar; Diana Agatha Nainggolan; Ira Syafitri Siregar; Ismaina Hamda (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Citizenship Education (PKn) is considered an important subject in forming the character and awareness of citizens, especially at the elementary school level. However, Civics teaching is often faced with various challenges, such as lack of student interest and limited resources. This research aims to evaluate Civics teaching practices at State Elementary School 060939 Medan Amplas, with a focus on approaches, teaching strategies, and challenges faced by Civics teachers. This research used a qualitative approach by conducting in-depth interviews with four Civics teachers at the school. Data were analyzed descriptively to identify the main themes that emerged from the interviews. The research results show that Civics teachers use an interactive and participatory approach in their teaching, with a focus on instilling moral and ethical values in students. However, there are still challenges such as lack of student interest and limited resources that need to be overcome. Recommendations for improving Civics teaching include training and professional development for teachers, use of varied teaching methods, involvement of parents and the community, and ongoing monitoring of teaching quality.